Analisis Kemampuan Technological Pedagogical Content Knowledge Mahasiswa Calon Guru Kimia - Maria Ulfah*; Erlina Erlina (Universitas Syiah Kuala, 2022)
The effectiveness of a learning is determined by the combination of various dimensions of knowledge with technology carried out by teachers. This study aims to analyse the TPACKs’ skills of chemistry education students of FKIP Untan who will become the future chemistry teachers. The method employs in this study is descriptive. The participants involved in this research are the students of the class 2019 and 2020. The instrument used is the TPACK questionnaire which consist of 7 indicators. The results obtained from data analysis are that all aspects of students’ TAPCK are in good category with scores for each aspect TK, CK, PK, PCK, TCK, TPK and TPACK with successive values of 75.01, 73.52, 72.08, 70.36, 72.54, 78.43, and 72.43. The integration of the dimensions of content knowledge, technology and pedagogy is very necessary to become a teacher, especially for chemistry education students who will become the future chemistry teachers